2002
DOI: 10.1021/bi011928m
|View full text |Cite
|
Sign up to set email alerts
|

The Somatostatin-28(1−12)-NPAMAP Sequence:  An Essential Helical-Promoting Motif Governing Prosomatostatin Processing at Mono- and Dibasic Sites

Abstract: Proline residues, known to have special structural properties, induce particular conformations which participate in some biological functions. Two prolines (Pro(-9), Pro(-5)) located near the processing sites (Arg(-15) and Arg(-2)Lys(-)(1)) of human prosomatostatin were previously shown to be important for cleavage of the precursor into somatostatin-28 (S-28) and somatostatin-14 (S-14) [Gomez et al. (1989) EMBO J. 8, 2911-2916]. In this study, the importance of the pentapeptide P-A-M-A-P sequence (P-(X)(3)-P p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 65 publications
1
12
0
Order By: Relevance
“…7a, deletion of Pro residues (motif XAMAX) or shift of Pro -5 (motif PAMPA) increased both the helicity values per residue and the size of the domain containing the dibasic site, i.e., Som(Asn -6 -Asn ?5 ). Since Pro -5 is highly conserved in the primary sequence of prosomatostatin from various species, this amino acid residue additionally plays a role in the correct folding of the prosomatostatin processing domain [89]. These conclusions were supported by the results obtained for the processing of prosomatostatin mutants D[AMA] and [P -6 P -5 ].…”
Section: Role Of Pro-(xaa) 3 -Pro Motif In the Conformation Of S-28(1mentioning
confidence: 59%
See 2 more Smart Citations
“…7a, deletion of Pro residues (motif XAMAX) or shift of Pro -5 (motif PAMPA) increased both the helicity values per residue and the size of the domain containing the dibasic site, i.e., Som(Asn -6 -Asn ?5 ). Since Pro -5 is highly conserved in the primary sequence of prosomatostatin from various species, this amino acid residue additionally plays a role in the correct folding of the prosomatostatin processing domain [89]. These conclusions were supported by the results obtained for the processing of prosomatostatin mutants D[AMA] and [P -6 P -5 ].…”
Section: Role Of Pro-(xaa) 3 -Pro Motif In the Conformation Of S-28(1mentioning
confidence: 59%
“…Analysis of the processing efficiencies, observed with either the non-mutated precursor and prosomatostatin mutants in transfected Neuro2A cells ( Table 2), indicated that substitution of Pro -5 by an a-helix promoting amino acid residue ([A -5 ] mutant) abolished cleavage at the dibasic site [63,82]. In contrast, replacement of Pro -5 by a b-turn ''former'' residue-like ([G -5 ] mutant) or of the sequence Pro -5 -Arg-Glu-Arg -2 by non-homologous peptide stretches ([S -5 -N -3 ] and [Y -5 -G -3 ] mutants), known to organize as b-turn structures in proteins, did not affect prosomatostatin processing [89].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently the role of a short helix-promoting sequence at the N-terminus of the multibasic cleavage site in governing the proteolytic processing was also emphasized for pro-somatostatin. [33] Structural studies are in progress on other HIV-1 gp160 cleavage site analogues to further investigate the structural factors that play a role in gp160-proteolytic enzyme recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Prepro-SS has a sequence of hydrophobic aa at the N-terminus which is cleaved at the gly-ala junction at position -78 (from the N-terminus to the Cterminus). Pro-SS undergoes both monobasic (Arg -15 ) and dibasic (Arg -2 Lys -1 ) cleavages to release the two biofunctional hormones SS-28 and SS-14 (Funckes et al, 1983;Brakch et al, 2002) (Figure 1). …”
mentioning
confidence: 99%